PREMARITAL SEXUAL BEHAVIOR OF ADOLESCENT IN THE PUBLIC SENIOR HIGH SCHOOL (SMAN) 9 BANJARMASIN - R Topan Aditya Rahman; Esti Yuandari (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: As it develops, teenagers begin to explore with themselves, the values of their role identity and behavior. Various factors also influence the behavior change of adolescent life both internal factor and external factor. If this is not addressed carefully, adolescents will be increasingly exposed to unhealthy reproductive problems, such as premarital sex that has a good impact, physical impact, psychological impact and psychosocial impact of the teenager.Purpose: This study aims to identify or explore sexual behavior in adolescents, the background of students perform the premarital sexual behavior, information sources used by adolescents to obtain information about premarital sex behavior, knowledge, values and norms, and the role of parents and schools to prevent premarital sex behavior.Method: This research used a qualitative method with the explorative descriptive approach. Sampling was collected by purposive sampling and snowball sampling. The sample of the research were students of SMAN 9 Banjarmasin class XI and XII, Religion Teachers, Counseling Teacher and Parents of teenagers who have conducted premarital sexual behavior.Result: Premarital sex behavior among adolescents is due to various backgrounds. This is influenced by internal factors (lack of adolescent knowledge about reproductive health and sex education) and external factors (lack of parent and school roles in preventing premarital sex behavior, misinformation sources used by adolescents to gain knowledge about reproductive health so that youth obtain information negative about reproductive health and the shift of values and norms about premarital sexual behavior among adolescents).Conclusion: Premarital sex behavior that rampantly occurs in adolescents caused by several reasons or background. Teenagers engage in premarital sexual behavior as a proof or a sign of their affection for their spouses, the expectation of their partner, they are often in the community of their peers so that adolescents follow the values of their peers who consider premarital sex to be common and prevalent during dating.Â Keywords: Adolescent, Behavior, Knowledge, Premarital, Role of parentsÂ